Novel soft-switching DC-DC converter with full ZVS-range and reduced filter requirement. I. Regulated-output applications. - Ayyanar, R. (IEEE Transactions on power electronics)
A novel soft-switching topology for DC-DC converters is proposed. It is well suited for applications in the range of a few hundred watts to a few kilowatts. It is essentially a hybrid combination of an uncontrolled half-bridge section and a phase-shift controlled full-bridge section, realized with just four switches. The main features of the proposed topology are zero-voltage-switching down to no-load without serious conduction loss penalty, constant frequency operation and, near-ideal filter waveforms. The improved filter waveforms result in significant savings in the input and output filter requirement, resulting in high power-density. The new topology requires two transformers and two DC-bypass capacitors. The combined VA rating of the two transformers is more than that of the single transformer of conventional full-bridge converters, for variable-input applications. In Part I of the paper, the converter operation is analyzed for typical switch-mode power supply applications, where the input voltage varies widely but the output voltage is fixed and is well regulated. Experimental results obtained from a 100 W/200 kHz proof-of-concept prototype confirm the superior features of the proposed hybrid configuration